Preparation for prenatal decision-making: a baseline of knowledge and reflection in women participating in prenatal screening. (March 2013) - McCoyd, Judith L. M.
Abstract: Objective : This prospective study gathered baseline information about knowledge and intentions regarding prenatal testing from women attending their nuchal translucency (NT) ultrasound and first sequential blood screen. Method : Surveys including questions about pregnancy history and hypotheticals about fetal diagnoses were distributed to all willing participants at an urban hospital and a suburban medical building during the waiting time for the NT ( N = 659). Results : The majority "never thought anything could be wrong" with their fetus and had not talked with the father or the health providers about that possibility. Presented with varied fetal diagnoses, the larger group nearly always "had the baby", except in the case of a fatal condition where 28% said they would have the baby in contrast to 26% who would end the pregnancy (remainder undecided). Hypotheticals about varied fetal conditions were generally "undecided" by a quarter to nearly half of the respondents. Conclusion : Women's baseline knowledge and reflection about the nature of prenatal screening and diagnosis are minimal in contrast to the large impact positive results could have on their lives. Providers need to weigh the benefit of priming decision-making by exposing women to the possibility of fetal diagnosis, against the cost of raised anxiety.